Atazanavir Exposure is Effective during Pregnancy Regardless of Tenofovir Use. Issue 1 (January 2015) - Colbers, Angela; Hawkins, David; Hidalgo-Tenorio, Carmen; Van Der Ende, Marchina; Gingelmaier, Andrea; Weizsäcker, Katharina; Kabeya, Kabamba; Taylor, Graham; Rockstroh, Jürgen; Lambert, John; Moltó, José; Wyen, Christoph; et al.
Background: We studied the effect of pregnancy on atazanavir pharmacokinetics in the presence and absence of tenofovir. Methods: This was a non-randomized, open-label, multicentre Phase IV study in HIV-infected pregnant women recruited from European HIV treatment centres. HIV-infected pregnant women treated with boosted atazanavir (300/100 mg or 400/100 mg atazanavir/ ritonavir) as part of their combination antiretroviral therapy (cART) were included in the study. 24 h pharmacokinetic curves were recorded in the third trimester and postpartum. Collection of a cord blood and maternal sample at delivery was optional. Results: 31 patients were included in the analysis, 21/31 patients used tenofovir as part of cART. Median (range) gestational age at delivery was 39 weeks (36–42). Approaching delivery 81% (25 patients) had an HIV viral load <50 copies/ml, all <1, 000 copies/ml. Least squares means ratios (90% CI) of atazanavir pharmacokinetic parameters third trimester/postpartum were: 0.66 (0.57, 0.75) for AUC0-24h, 0.70 (0.61, 0.80) for Cmax and 0.59 (0.48, 0.72) for C24h . No statistical difference in pharmacokinetic parameters was found between patients using tenofovir versus no tenofovir. None of the patients showed atazanavir concentrations <0.15 mg/l (target for treatment-naive patients). One baby had a congenital abnormality, which was not likely to be related to atazanavir/ritonavir use. None of the children were HIV-infected. Conclusions: Despite 34% lower atazanavir exposure during pregnancy, atazanavir/ritonavir 300/100 mg once daily generates effective concentrations for protease inhibitor (PI)-naive patients, even if co-administered with tenofovir. For treatment-experienced patients (with relevant PI resistance mutations) therapeutic drug monitoring of atazanavir should be considered to adapt the atazanavir/ritonavir dose on an individual basis. ClinicalTrials.gov number NCT00825929.